Greek Antiquity in Schiller's "Wallenstein" - Berns, Gisela N. (UNC Studies in the Germanic Languages and Literatures, 1985)
An exploration of the poetic function of Greek archetypes in Schiller's "Wallenstein", this study claims Homer's "Iliad" and Euripides's "Iphigenia in Aulis", the first epic and the last tragic poem about the Trojan War in the Greek tradition, as archetypal sources for Schiller's modern historical drama about the Thirty Years War. In close comparison with Voss's translation of the "Iliad" and Schiller's own translation of "Iphigenia in Aulis", Berns shows how "Wallenstein" compounds echoes of Homeric and Euripidean characters and plots to create a rich horizon of mythical overtones above and beyond the historical world.